An assessment of the home management training needs of domestic workers in selected regions of the Ethekwini Municipal Area - Ngidi, Buyisiwe Ethel (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2003.